Influence of Microenvironment on Mesenchymal Stem Cell Therapeutic Potency: From Planar Culture to Microcarriers - Tsai, Ang-Chen; Jeske, Richard; Chen, Xingchi; Yuan, Xuegang; Li, Yan (Frontiers in Bioengineering and Biotechnology, 2020)
Human mesenchymal stem cells (hMSCs) are a promising candidate in cell therapy as they exhibit multilineage differentiation, homing to the site of injury, and secretion of trophic factors that facilitate tissue healing and/or modulate immune response. As a result, hMSC-derived products have attracted growing interests in preclinical and clinical studies. The development of hMSC culture platforms for large-scale biomanufacturing is necessary to meet the requirements for late-phase clinical trials and future commercialization. Microcarriers in stirred-tank bioreactors have been widely utilized in large-scale expansion of hMSCs for translational applications because of a high surface-to-volume ratio compared to conventional 2D planar culture. However, recent studies have demonstrated that microcarrier-expanded hMSCs differ from dish- or flask-expanded cells in size, morphology, proliferation, viability, surface markers, gene expression, differentiation potential, and secretome profile which may lead to altered therapeutic potency. Therefore, understanding the bioprocessing parameters that influence hMSC therapeutic efficacy is essential for the optimization of microcarrier-based bioreactor system to maximize hMSC quantity without sacrificing quality. In this review, biomanufacturing parameters encountered in planar culture and microcarrier-based bioreactor culture of hMSCs are compared and discussed with specific focus on cell-adhesion surface (e.g., discontinuous surface, underlying curvature, microcarrier stiffness, porosity, surface roughness, coating, and charge) and the dynamic microenvironment in bioreactor culture (e.g., oxygen and nutrients, shear stress, particle collision, and aggregation). The influence of dynamic culture in bioreactors on hMSC properties is also reviewed in order to establish connection between bioprocessing and stem cell function. This review addresses fundamental principles and concepts for future design of biomanufacturing systems for hMSC-based therapy.